Methodological and Ethical Considerations in Research Involving Adult Survivors of Childhood Sexual Abuse : A Reflection - Nurul Eka Hidayati; Nugroho, Fentiny; Sali Rahadi Asih (Asean Social Work Journal, 2022)
The number of reported incidents of sexual violence continues to increase in Indonesia, giving rise to deep concerns and calls to prevent sexual violence from occurring in the future. Some experts call it “the Silent Epidemic” because it is estimated that the actual number of events is much higher than reported. Therefore, research on this issue needs to be continued to get input on the cause and effect, impact and prevention efforts. Researches on child sexual abuse and the impact throughout the lives of the survivors is highly important in providing scientific evidences for developing the interventions in social work practice. However, it also comes with very specific challenges when conducting a research on this issue. There are no specific guidelines regarding ethics and methodology in carrying out research on survivors of sexual violence.  Therefore, in the future it is important to consider the methodological and ethical aspects before embarking on a research involving survivors of sexual violence. Based on the experience of carrying out this research, the aspects that potentially harm or put participants and researchers at risk can be minimized or even avoided. This experience can also provide reinforcement that research involving trauma survivors can benefit both the affected population as well as social work scientists and practitioners. This manuscript discusses the current thinking on these issues.